Development of a nano-emulsion based multivalent protein subunit vaccine against Pseudomonas aeruginosa - Howlader, Debaki R.; Mandal, Rahul Shubhra; Lu, Ti; Maiti, Suhrid; Dietz, Zackary K.; Das, Sayan; Whittier, Sean K.; Nagel, Aaron C.; Biswas, Satabdi; Varisco, David J.; Gardner, Francesca M.; Ernst, Robert K.; et al. (Frontiers in Immunology, 2024)
Pseudomonas aeruginosa (Pa) is an opportunistic bacterial pathogen responsible for severe hospital acquired infections in immunocompromised and elderly individuals. Emergence of increasingly drug resistant strains and the absence of a broad-spectrum prophylactic vaccine against both T3SA+ (type III secretion apparatus) and ExlA+/T3SA- Pa strains worsen the situation in a post-pandemic world. Thus, we formulated a candidate subunit vaccine (called ExlA/L-PaF/BECC/ME) against both Pa types. This bivalent vaccine was generated by combining the C-terminal active moiety of exolysin A (ExlA) produced by non-T3SA Pa strains with our T3SA-based vaccine platform, L-PaF, in an oil-in-water emulsion. The ExlA/L-PaF in ME (MedImmune emulsion) was then mixed with BECC438b, an engineered lipid A analogue and a TLR4 agonist. This formulation was administered intranasally (IN) to young and elderly mice to determine its potency across a diverse age-range. The elderly mice were used to mimic the infection seen in elderly humans, who are more susceptible to serious Pa disease compared to their young adult counterparts. After Pa infection, mice immunized with ExlA/L-PaF/BECC/ME displayed a T cell-mediated adaptive response while PBS-vaccinated mice experienced a rapid onset inflammatory response. Important genes and pathways were observed, which give rise to an anti-Pa immune response. Thus, this vaccine has the potential to protect aged individuals in our population from serious Pa infection.